RIÉ 277: An Inscription of the Time of Ptolemy II? - Liuzzo, Pietro Maria (Aethiopica, 2019)
The article suggests that the inscription known as RIÉ 277 might be a Hellenistic inscription of the period of Ptolemy II Philadelphus. This interpretation is based on a revision of the main hypotheses concerning the geographical centre suggested by the text.